Language of Light : A Survey of the Photography Collection of the University of Kansas Museum of Art. (Kansas : The University of Kansas Museum of Art, 1974)
Adams, Ansel ; Alinder, Jim ; Arbus, Diane ; Barrow, Thomas ; Bellocq, E.L. ; Berenson, Betty ; Blackwell, Ben ; Brassaï ; Callahan, Harry ; Cosindas, Marie ; Cunningham, Imogen ; Draper, John W. ; Flachéron, Comte F. ; Frith, Francis ; Heinecken, Robert ; Krims, Leslie ; Michalik, Chester ; Payton, Leland ; Smith, W. Eugene ; Uelsmann, Jerry ; Welpott, Jack ; Weston, Edward
Language of Light : A Survey of the Photography Collection of the University of Kansas Museum of Art, The University of Kansas Museum of Art, Kansas, February 3 - February 24, 1974
boek